Nonlocalized postactivation performance enhancement (PAPE) effects in trained athletes: a pilot study - Cuenca-Fernández, F.; Smith, I. C.; Jordan, M. J.; MacIntosh, B. R.; López-Contreras, G.; Arellano, R.; Herzog, W. (Applied Physiology, Nutrition, and Metabolism, 2017)
Fifteen trained athletes were assessed for postactivation performance enhancement (PAPE) of squat jumps (SJs) and power push-ups (PPUs) following upper body activation, lower body activation, upper and lower body activation, and rest. SJ improved similarly across all 4 conditions. PPU could not be assessed. Since the test protocol of SJ and PPU involved upper and lower body activation and caused PAPE in SJ, future work is required to determine if a nonlocalized PAPE effect exists.